Mobile robot positioning system - Khairulnizam Othman (Universiti Malaysia Perlis, 2008)
The report has examined the design, development and implementation of 4 Wheels Mobile Robots that implemented with Positioning System that can perform nonconventional maneuver. The report presents the process undertaken in the design and development of the Mobile Robot Positioning with using 4 wheels (manufacture by Streamline design Inc.). Using these 4 Wheels drive, the Mobile Robots positioning provide 2 Degree of Freedom (DOF) for the mobility. Attention also paid for the development of kinematics and dynamic controlling schemes, which taken for the Odometry is based on simple equations which holds true when wheel revolutions can be translated accurately into linear displacement relative to the floor. All 4 wheel will rotate with, 2 wheels will rotate simultaneously at the right side which power with using dc motor same goes to the left side. The dc motor that we used is high torque dc motor. This will give a good controlling speed. A two channel high power H-bridge circuit using one unit of L293D motor driver. This component is build with complete circuit interface to a Parallax Basic Stamp (BS2) microcontroller module. Several motion control algorithm using BS2 software was develop to test the capabilities of system mobile motion in Y axis, X axis and other, particular attention is paid to evaluate the ability of the using Odometry to detect and correct positioning of the mobile platforms from 4 point. Data from the experiment was used as the discussion for the result and future works of the project. The Mobile Robot Positioning System using 4 wheels provide a convenient platform for future development in robotic. The combination of mechanical design of motor attach thru gear to the wheels and encoder for detecting angle and acceleration both side also give us good controlling method. This combination of mechanical design, controlling method (H- Bridge) and multiple input and output of sensor allow the exploration of large number in the implementation for control algorithm and software to the practical of Positioning System to the real life.